2022
DOI: 10.3390/su14094991
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Climatic Factors on the Phenology of Chokeberry Cultivars Planted in the Pedoclimatic Conditions of Southern Romania

Abstract: This paper aimed to study the adaptation of a crop to the specific climatic conditions of southern Romania, Pitești-Mărăcineni, Romania, in terms of the phenology of two chokeberry (Aronia melanocarpa) cultivars (‘Melrom’ and ‘Nero’). The BBCH (Biologische Bundesantalt, Bundessortenamt and Chemische Industrie) scale was used for phenological observations. The recorded data were statistically processed, calculating the average onset time and duration of fruiting phenophases and dormancy duration, average air te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
(37 reference statements)
1
0
0
Order By: Relevance
“…'Nero' and 'Melrom' are two of the most commonly cultivated chokeberry cultivars in Romania. The chokeberry cultivars are adapted to different environmental conditions in Romania, even the low temperatures during the dormancy stage (-14.1°C) and bud burst (-6.2°C), as well the high temperatures during the summer did not damage the flower buds as observed and reported by (Diaconescu et al 2022). Chokeberry adaptation to different environmental conditions is a dynamic process, which is correlated with ambient temperatures, solar radiation, rainfall and soil type.…”
Section: Introductionsupporting
confidence: 52%
“…'Nero' and 'Melrom' are two of the most commonly cultivated chokeberry cultivars in Romania. The chokeberry cultivars are adapted to different environmental conditions in Romania, even the low temperatures during the dormancy stage (-14.1°C) and bud burst (-6.2°C), as well the high temperatures during the summer did not damage the flower buds as observed and reported by (Diaconescu et al 2022). Chokeberry adaptation to different environmental conditions is a dynamic process, which is correlated with ambient temperatures, solar radiation, rainfall and soil type.…”
Section: Introductionsupporting
confidence: 52%
“…Light, temperature and humidity are the major environmental factors influencing the plant physiological functions [24,25], photosynthesis and hormonal balance [26] and key active processes in plants life [27,28] including the transition from one development stage to the next [29,30,31] . Besides environmental issues, edaphic elements also have remarkable influence on plant growth and development [32] as soil nutrient availability is one of the absolute needs of plants [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Phenological observations obtained a BBCH value of 53-87, while the mean air temperature over 154 days was reported to vary from 6.1 to 36.8°C. At the end of this research, they identified that chokeberry (Aronia melanocarpa) was a berry fruit species that was adapted to the temperate continental climate of south Romania [53].…”
Section: Black Chokeberry (Aronia Melanocarpa Michx)mentioning
confidence: 99%